2021
DOI: 10.1016/j.isci.2021.103532
|View full text |Cite
|
Sign up to set email alerts
|

Review of strategies toward the development of alloy two-dimensional (2D) transition metal dichalcogenides

Abstract: Summary Atomically thin two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted significant attention owing to their prosperity in material research. The inimitable features of TMDCs triggered the emerging applications in diverse areas. In this review, we focus on the tailored and engineering of the crystal lattice of TMDCs that finally enhance the efficiency of the material properties. We highlight several preparation techniques and recent advancements in compositional engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…In many 2D materials, alloying of both cations and anions has been shown to be a good way to preferentially stabilize metastable phases and tune their properties. 62,[78][79][80] To determine the most energetically favorable Sr/Y position in each alloy we tested all possible relative orientations and took the lowest energy one; all structures tested at each concentration in the mixed and asymmetric phases are shown in ESI Fig. S28 and S29, † respectively, with the lowest energy one highlighted.…”
Section: External Strain and Alloyingmentioning
confidence: 99%
“…In many 2D materials, alloying of both cations and anions has been shown to be a good way to preferentially stabilize metastable phases and tune their properties. 62,[78][79][80] To determine the most energetically favorable Sr/Y position in each alloy we tested all possible relative orientations and took the lowest energy one; all structures tested at each concentration in the mixed and asymmetric phases are shown in ESI Fig. S28 and S29, † respectively, with the lowest energy one highlighted.…”
Section: External Strain and Alloyingmentioning
confidence: 99%
“…43 A relatively high doping amount can enable the formation of TMD alloys, which manifest structures between two different TMDs. 45 Besides chalcogen dopants with discrepancy in their atom radius and charge density, doped transition metal atoms are likely to induce the phase transition in the original TMDs, which is derived from the distinguished coordination of transition metals with extra valence electrons. For example, MoS 2 flakes with doped Re or Fe atoms are transformed from the original 1H phase to the 1T phase 46,47 because the extra valence electrons of Re and Fe dopants induce altered orbital splitting on account of the crystal field theory.…”
Section: Point Structuresmentioning
confidence: 99%
“…The recently discovered in-plane chemically ordered MAX phase alloy called i-MAX phase is an example [71][72][73]. A remarkable feature of i-MAX phase is that the two-dimensional MXene obtained by different etching methods can be chemically ordered in plane or vacancy ordered, which has great application prospects for catalysis and energy storage [74][75][76][77][78][79][80][81]. Encouraged by the i-MAX phase discovered earlier, Martin et al [82] theoretically identified 15 novel MAB phases with in-plane chemical order, called i-MAB phases (Fig.…”
Section: Introductionmentioning
confidence: 99%